Globba ruiliensis (Zingiberaceae), a new synonym of G. multiflora - Jin, Jia Yi; Chen, Juan; Bai, Lin (Phytotaxa, 2024)
Based on an examination of herbarium specimens and fresh materials, it is confirmed that Globba ruiliensis is conspecific with G. multiflora. The former is treated as a synonym of the latter. Globba multiflora is newly recorded from Xizang, China. A lectotype is designated for G. multiflora. Taxonomic notes on this species are also provided.